Seed‐Based Rehabilitation of Phytophthora cinnamomi‐Infested Forest Sites - Himbutugoda S. Harshani; Todd E. Erickson; Jen McComb; Treena Burgess; Giles Hardy (Ecology and Evolution, 2025)
ABSTRACT The plant pathogen Phytophthora cinnamomi has significantly damaged the floristic diversity and community structure of the jarrah (Eucalyptus marginata) forest in Western Australia. Complete eradication of the pathogen from infested sites is not possible. This study assessed the feasibility of rehabilitating P. cinnamomi‐infested forest sites with native resistant species using various methods of seed deployment. Precision burial of seeds at 5 mm was used as a control, mimicking optimum recruitment depths for many native species and compared against the use of extruded pellets (hereafter ‘pellets’) as an alternative method of precision seed placement. Eighteen rehabilitation plots were set up in three P. cinnamomi‐infested reserves using six species. For Acacia acuminata, A. saligna, Calothamnus sanguineus and Melaleuca seriata, there were three treatments: precision buried (non‐pelleted) seeds, pellets and pellets with an additive (i.e., a rhizobium bacterium for the Acacia spp. and ectomycorrhizal fungus spores for C. sanguineus and M. seriata). Banksia sessilis and Hakea laurina had only two treatments: precision buried (non‐pelleted) seeds and pellets. Seedlings of all six species emerged successfully in P. cinnamomi‐infested sites, and the numbers ranged between 23% and 88%. The survival of emerged seedlings after 9 months ranged between 16% and 84%, except M. seriata, which emerged at 59% but failed to survive. In most species, except A. acuminata, seedling emergence and survival from pellets were similar and within an acceptable seedling establishment range when compared to non‐pelleted seeds. Pelletised seed with the addition of beneficial microbes did not improve seedling survival or shoot growth in the diseased areas of the jarrah forest. Overall, the results suggest that seedlings of resistant native species can successfully establish in P. cinnamomi‐infested sites and pelletised seeds can be used as a viable method for precision planting.